PERANCANGAN DASHBOARD LAPORAN PENJUALAN PADA TOKO HBI - Franz Kevin (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
HBI is an accessories store that sells women's jewelry accessories. HBI Shop sells various women's jewelry products such as bracelets, rings, necklaces, earrings and other custom accessories. Each sales activity must have a sales document that contains information about sales reports. sales reports at HBI Stores still use Microsoft Excel, so it takes a long time to get information about sales report developments. Increasing product sales requires implementing a business strategy to improve the quality of the company, such as packaging it into a visualization on the dashboard. Dashboard is a tool for presenting concise information in diagrams, visual indicators, or graphics in the form of information. The purpose of this dashboard design is to form a sales report visualization display that users can use to see the situation in the company's sales reports. The data used is sales data from 2021 to 2022. The dashboard design method that will be used is the prototyping method. The sales report results visualized are in the form of a sales report dashboard at the HBI Store which can make it easier for HBI Shop owners to find out information on sales reports and assist companies in making decisions.